Rising commodities prices driven by the Russia-Ukraine crisis threaten to undermine Kenya’s economy, increase poverty - Breisinger, Clemens; Xinshen Diao; Dorosh, Paul A.; Mbuthia, Juneweenex; Omune, Lensa; Ombui Oseko, Edwin; Pradesha, Angga; Thurlow, James (International Food Policy Research Institute, 2022)
Much of the early attention on the Russian-Ukraine conflict’s food security impacts has been concentrated on countries highly dependent on wheat imports from the Black Sea region. Given the important role that wheat products play in the diets of people in Egypt, Sudan, Yemen, Lebanon, and other countries, the interruption in Black Sea wheat trade and high prices have raised serious concerns about rising levels of food insecurity, poverty, and instability around the world.